Pembentukan model Al-Qalb dalam komponen ijtihadik bagi program Ulul Albab - Muhammad Zickryl Hakim, Roslan (2025)
This study aims to form an al-Qalb model for improving the ijtihadik component in an Islamic educational program, namely Program Ulul Albab. This is because al-Qalb has significant intellectual potential regarding the ijtihadik component. Previous studies stated that there is a need for improving the ijtihad component based on the less favorable results. Thus, this study has three objectives: first, to identify the concept of al-Qalb in the construction of ijtihadik elements; second, to analyze the form of implementation of the ijtihadik component in the Program Ulul Albab; and third, to form the al-Qalb model in the implementation of the ijtihadik component of the Program Ulul Albab. The research approach used in this study is qualitative, with an exploratory research design. Data from documentation and interviews were analysed using content analysis methods. A total of 11 respondents from Maktab Rendah Sains Mara (MRSM) Kepala Batas and Sekolah Menengah Kebangsaan Agama Kedah participated in this study. The study’s results found that no specific modules were used in implementing ijtihadik in both institutions. The existing approaches are more focused on physical development. Meanwhile, the theoretical approach based on Bloom's Taxonomy is less appropriate and less effective in developing ijtihadik. Thus, this study contributes to the Program Ulul Albab in the implementation of ijtihadik components based on the cognitive and affective domains of al-Qalb from an Islamic perspective, along with the purification of the heart (tazkiyat al-Qalb) from negative elements.